Action painting under spectroscopic light: Excited-state exchange interactions behind the vibrant blue in Jackson Pollock’s Number 1A, 1948 - Alexander J. Heyer; Abed Haddad; Racquel Scott; Glen Kowach; Edward I. Solomon (Proceedings of the National Academy of Sciences, 2025)
Number 1A, 1948 by Jackson Pollock is a quintessential example of his action painting technique where ropes of color, drips of black, and pools of white coalesce into the layered dynamism that defines his style. While past work has identified the red and yellow pigments that form part of his core palette, the vibrant blue in the painting has remained unassigned. In this study resonance Raman spectroscopy is used to assign the blue in the painting as manganese blue. This assignment offers critical context for the conservation of his works. Importantly, assignment of this pigment enables spectroscopic investigation of the electronic structure origin of the pure hue of manganese blue and the chemical phenomena that produce its color. To probe these phenomena, resonance Raman data are coupled to magnetic circular dichroism spectroscopy and density functional theory calculations to assign and analyze the two electronic transitions that create the blue color. This study reveals these bands are split by excited-state exchange interactions; the gap between them contains the reflected light that gives manganese blue its appearance. This sheds light on distinct advantages of molecular inorganic pigments: their ability to leverage ligand field effects in charge transfer states to create multiple intense visible absorption features and the ability to fine-tune pigment color through host lattice electrostatics.